Integration of Eco-Islamic Values and Local Wisdom of the Suku Anak Dalam: A Model for Conservation Education and Cultural Resilience Strengthening - Pahmi Pahmi; Alhusni Alhusni; Khaidir Ali; Mukhlas Nugrah (Tunjuk Ajar: Journal of Education and Culture, 2026)
This study analyzes the integration of Eco-Islamic values with the local wisdom of the Suku Anak Dalam (SAD) in Jambi to develop a culture-based conservation education model. Through a qualitative ethnographic approach involving in-depth interviews, participant observation, and document analysis, the research reveals that the ecological practices of SAD, such as hompongan (customary forest enclosures), tanah peranakan (ancestral land conservation), and the besale ritual, not only represent environmental ethics aligned with Islamic principles (kalifah, amanah, mizan, ‘adl) but also contain rich pedagogical values. This integration gives rise to an Eco-Islamic Indigenous Framework, which is operationalized into a culture-based conservation education model. This model offers a contextual learning approach to strengthen ecological literacy, cultural identity, and community resilience. The study concludes that integrating spiritual values and local wisdom into conservation education can be an effective strategy for achieving environmental and cultural sustainability simultaneously.